Uma interpretação do espaço geográfico a partir das manifestações culturais em São Gonçalo Beira Rio, Cuiabá - MT : as práticas culturais do lugar e seus contextos - Corrêa, Thamires Cristine (2018)
Culture may be understood through several conceptions, and, in many cases, it is considered as derivative of the way of life of a population, that is, it refers to a set of values, beliefs, knowledge and customs that characterize and differentiate human groups, its maintenance is linked to the transmission of their aspects between generations in historical time. However, the maintenance of culture and its aspects can become problematic in the face of possible socioeconomic and political changes occurring in the geographic space. The ways of organizing, manifesting, living in the place, and that guarantee through everyday life the identity of social groups, can be lost or partially re-signified over time. In this context, we will seek to analyze and discuss the genesis of the cultural aspects that define the singularity of São Gonçalo Beira Rio community, located in the city of Cuiabá-Mato Grosso, founded in the 18th century. In general terms, the historical aspects associated with fishing, ceramic handicrafts, dance (siriri and cururu) and Festa de São Gonçalo will be analyzed, highlighting their resignifications that have been linked in time, and in several cases are linked to the emergence of new political, economic and social demands, evidenced by a global scale of influence. For such, in methodological terms, historical documents and specific works were consulted, as well as fieldwork with interviews with the community’s residents.